PENGARUH VARIASI PENDINGIN TERHADAP KEKUATAN BENDING PADA PENGELASAN TEE JOINT EQUALIZER TYPE YORK TRAILER - Akhmad Syarief; Baramsyah Baramsyah (Scientific Journal of Mechanical Engineering Kinematika, 2019)
In the present era of technological developments in the industrial world is growing and progressing. But in the industrial world can not be separated from the manufacturing process, especially in the field of welding, because welding has an important role in engineering or reparasi-raparasi associated with metal welding. And also a lot of welding is used in the field of design. The scope of welding use in construction is very wide including shipping industry, bridge, steel frame, heavy equipment, transportation facilities, pipeline and so forth. In the process of welding requires a person who is reliable or skilled in welding work, in order to produce good quality results. The highest value of bending stress is found on air cooling medium that is 2870,17 N/mm², And the lowest bending voltage value is in water cooling that is 2460,1 N/mm².. The highest shear stress value is in air cooling medium ie 197.96 N/mm², and the lowest shear stress value is in water cooling that is 169.68 N/mm². The bending voltage value allowed is the highest in the air conditioning medium 2474.5 N/mm², And the lowest permissible bending stress value is found in water cooling of 2121 N/mm².